Value chain of potato in Bukidnon and Kapatagan net margins, market options, and price analysis - Naparan, Rica Marie P.
This study attempts to examine the efficiency, distribution of benefits and the opportunities present in the value chain of potato in Bukidnon, Northern Mindanao and Kapatagan, Davao del Sur. Specifically, this study aims to achieve the following objectives: (1)to compare the performance of farmers in Bukidnon and Kapatagan; (2) to describe the activities and roles done by each actor of the supply chain and their possible contribution on price determination; (3) compare the profitability and allocation of cost in per kilogram of potato being traded as well as the distribution of benefits and problems among the supply chain actors; and (4) to explain how prices of potato are being set in the market considering the different factors affecting prices beyond supply and demand. Value chain mapping, net margins analysis and descriptive presentation on how prices are set in the market were used to achieve the objectives. Farmers from Kapatagan and Bukidnon as well as the traders of their most prevalent market destination were covered in the study. Results show that in terms of farm production, Kapatagan farmers were more efficient compared to Bukidnon farmers. Davao City market was the most profitable market destination for Kapatagan, while Cagayan de Oro City was the common market destination of Bukidnon. Farmers and traders formulate the price at the wholesale market through supply and demand estimation and the level of market information may affect individual price negotiations. The price formation process was primarily based on the traders' experience and other factors such as seasonality of demand and the quality of market information.